The role of public enterprises in economic development in Nigeria - Anike, Happiness Ozioma Obi; Okafor, Chikodili Nkiruka; Udejinta, Nnaemeka Beneth (International research journal of management, IT and social sciences, 2017)
The study focuses on the role of public enterprises in economic development in Nigeria. The study sought to ascertain the role of public enterprises in improving the standard of living in Nigeria, to determine the nature of the relationship between Public enterprises and employment generation, to ascertain challenges encounter by public enterprises in contributing to national development.The study had a population size of 340, out of which a sample size of 246 was realized using Taro Yamane’s formula at 5% error tolerance and 95% level of confidence. The instrument used for data collection was primarily questionnaire and interview. Out of 246 copies of the questionnaire that were distributed, 230 copies were returned while 16 were not returned. The survey research design was adopted for the study. The hypotheses were tested using the Pearson product moment correlation coefficient, Chi-square, and simple linear regression statistical tools. The findings indicated that Public enterprises significantly improve standard of living in Nigeria (r = 0.703; t =29.976; F= 898.558; p< 0.05).There is a positive relationship between Public enterprises and employment generation (r = .596, P<.05).